2013
DOI: 10.2310/jim.0b013e31829a7c1b
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Proliferative Plaque Formation in a Canine Model of Chronic Hypertension

Abstract: Carotid proliferative plaques were developed in a canine model of chronic hypertension induced by a novel vascular clip. The plaques were mainly comprised of smooth muscle cells, proteoglycans, and collagen fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Unlike humans, HDL is the most abundant lipoprotein in wild-type dogs [ 19 ]. The baseline plasma triglycerides and total cholesterol measured in this study were in consistent with the Tian's study [ 13 ]. However, in this present study, the LDL level in ApoE −/− dogs was approximately 35-40-fold that in wild-type dogs and became the main lipoprotein in plasma.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Unlike humans, HDL is the most abundant lipoprotein in wild-type dogs [ 19 ]. The baseline plasma triglycerides and total cholesterol measured in this study were in consistent with the Tian's study [ 13 ]. However, in this present study, the LDL level in ApoE −/− dogs was approximately 35-40-fold that in wild-type dogs and became the main lipoprotein in plasma.…”
Section: Discussionsupporting
confidence: 88%
“…By using the wild-type dogs as a normal control, we first established the normal reference values of diameter and IMT of the main arteries during the young (6–15 months) and adult periods (18–29 months) and found that along with growth, the diameters of CCA, ECA, CIA and aorta gradually increased in wild-type dogs. In addition, the IMT of CCA in wild type beagle dogs was approximately 0.3 mm, which was similar to the Tian's study on carotid proliferative plaque formation in a canine model of chronic hypertension (beagle dogs, n=5 for each group, age 12–15 months) [ 13 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation